ANALYSIS OF DONOR LOYALTY AT DOMPET DHUAFA INSTITUTIONS - Maliyana Maliyana; Alfatih S Manggabarani; Prasetyo Hadi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this research is to analyze the factors that are predictors of donor loyalty from the perspective of promotion and service quality with trust as a mediation, then applied to Dompet Dhuafa. Quantitative approach is applied in research by establishing causality design. There were 100 donors as the research sample which was determined by purposive sampling technique. Partial Least Square analysis was applied to test the debfab hypothesis with the help of the SmartPLS version 3.0 program. The results of the analysis show that: (1) Quality of service can significantly increase the trust and loyalty of Dompet Dhuafa donors, (2) Promotion can significantly increase the trust and loyalty of Dompet Dhuafa donors, (3) Trust can significantly increase the loyalty of Dompet Dhuafa donors, and (4) Trust mediates the influence of quality of service and promotion on the loyalty of Dompet Dhuafa donors. Keywords: Service Quality, Promotion, Trust, Loyalty